Supporting the Design of Technology-Mediated Sharing Practices - Fedosov, Anton (Carl Grossmann Verlag, 2020)
Online social networks have made sharing personal experiences with others a common activity. Furthermore, modern mobile apps, cloud services, and wearable technologies expanded the scope of shared content on the internet from personal media to individual preferences and activities to information about real-world things. This book explores these practices within two emergent sharing contexts: personal activity tracking and "sharing economy" services. It should be of interest not only to interaction design researchers who are critically examining technology-mediated sharing practices through fieldwork studies and design practitioners who are building and evaluating sharing economy platforms, but also to readers who are curious to explore the diversity of sharing practices in our everyday lives.